The Role of Moral Sensitivity in Moderating Factors for Preventing Village Fund Fraud - Pasaribu, Dompak; Sinaga, Enjelina; Panjaitan, Rike Yolanda; B. Siahaan, Septony; Napitupulu, Junika (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines the influence of the competence of village officials, government compliance in reporting, and internal control system on the prevention of misappropriation of village funds, with moral sensitivity as a moderation variable. This study uses a quantitative methodology to examine the relationship between stock prices (independent variables) and dependent variables—working capital turnover, profitability, liquidity, and solvency. Primary data involved 48 village devices selected through purposive sampling. Data collection was carried out through questionnaires that were distributed to village officials involved in the management of village funds and analyzed using descriptive statistics. Data quality was assessed through validity and reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS 26. The results showed that the competence of village officials and internal control systems had a significant effect on the prevention of misappropriation of village funds, while government compliance in reporting did not show a significant influence. Moral sensitivity moderates the relationship between the competence of village officials and compliance in reporting on the prevention of misappropriation of village funds, but does not moderate the relationship between the internal control system and the prevention of misappropriation of village funds